Vegetation resurveys of Dolomiti Bellunesi - Chiara; Alessandro; Marcello; Michele; Cesare; Gianni; Juri (Zenodo, 2022)
The dataset contains the resurvey of historical vegetation plots in the Dolomiti Bellunesi National Park. Resurvey data are focus on 59 plots sampled in four main vegetation types: 15 in the snowbeds with dominance of dwarf willows ( Salix herbacea L. or S. retusa L.) or Luzula alpinopilosa (Chaix) Breistr; 12 in the secondary alpine and subalpine acidophytic grasslands dominated by Nardus stricta L.; 19 in the primary mesophytic subalpine and alpine grasslands on neutral or base-rich soils dominated by Sesleria caerulea (L.) Ard. and Carex sempervirens Vill.; 13 in the Primary xerophytic subalpine and alpine grasslands on neutral or base-rich soils dominated by Sesleria caerulea and Helictotrichon parlatorei (J. Woods) Pilg. Historical plots were sampled from 1998 to 2003 while the resurvey was carried out from 2018 to 2019. These plots are scattered between 1320 and 2190 m a.s.l., mainly located inside the alpine life zone. For more information about the dataset please see the published paper https://doi.org/10.1080/11263504.2022.2100498